KAJIAN SOSIAL KARYA SENI KRIYA KAYU DI DESA MULYOHARJO KABUPATEN JEPARA - Yusuf, Suharto; Pambudi, Fivin Bagus Septiya (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2021)
The development of handicrafts in Indonesia is now experiencing such a rapid pace, especially those oriented to various modern technological facilities lately. Accompanying all human needs that are passive and have an active function, furniture or household furniture products are the main choice in various worlds of property today, both domestically and abroad. The relationship between craft art and several aspects that must be met shows the existence of a problematic in its embodiment. This is probably not realized by the kriyawan who appear instantly and oriented to a market. It's the same with craftsmen in Mulyoharjo Village, although there are those who have the idea of working through an artistic instinct and become unconventional craft craftsmen in their social community.